Why Tanzania is ahead - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
A journalist from Kampala and a researcher from Malawi visit Arusha?s Kilombero market. They are amazed by the variety and quantity of traditional African vegetables being sold here. They compare the market with the situation in their own countries, where many of the same plants are eaten, but they are seldom found in markets. They discuss what kind of people are buying, and how the vegetables can be cooked to preserve their nutritional content.